Complete mitochondrial genome of the Ictiobus cyprinellus (Actinopterygii: Ostariophysi). (2nd September 2016) - Liu, Xueqing; Du, Hejun; Wu, Chuan; Xiao, Kan; Qu, Huantao; Zhang, Xu; Gao, Yong; Chen, Lei
Abstract: The complete mitochondrial genome of Ictiobus cyprinellus was first determined by a polymerase chain reaction-based sequencing method in this study. The mitochondria was 16, 611 bp in length, including 13 protein genes, 2 ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes and 1 control region. All genes were encoded on the heavy strain except for ND6 and eight tRNA genes. The gene arrangement of I. cyprinellus was similar to those found in the other Catostomidae species. Base composition of the heavy strain was A (29.40%), T (24.86%), C (27.96%), G (17.78%) and with A + T bias of 54.26%.